Solar Simulated Ultraviolet Radiation Induces Global Histone Hypoacetylation in Human Keratinocytes. - Xiaoru Zhang; Thomas Kluz; Lisa Gesumaria; Mary S Matsui; Max Costa; Hong Sun (PLoS ONE, 2016)
Ultraviolet radiation (UVR) from sunlight is the primary effector of skin DNA damage. Chromatin remodeling and histone post-translational modification (PTM) are critical factors in repairing DNA damage and maintaining genomic integrity, however, the dynamic changes of histone marks in response to solar UVR are not well characterized. Here we report global changes in histone PTMs induced by solar simulated UVR (ssUVR). A decrease in lysine acetylation of histones H3 and H4, particularly at positions of H3 lysine 9, lysine 56, H4 lysine 5, and lysine 16, was found in human keratinocytes exposed to ssUVR. These acetylation changes were highly associated with ssUVR in a dose-dependent and time-specific manner. Interestingly, H4K16ac, a mark that is crucial for higher order chromatin structure, exhibited a persistent reduction by ssUVR that was transmitted through multiple cell divisions. In addition, the enzymatic activities of histone acetyltransferases were significantly reduced in irradiated cells, which may account for decreased global acetylation. Moreover, depletion of histone deacetylase SIRT1 in keratinocytes rescued ssUVR-induced H4K16 hypoacetylation. These results indicate that ssUVR affects both HDAC and HAT activities, leading to reduced histone acetylation.